2018
DOI: 10.1101/288035
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lipid utilization in skeletal muscle cells is modulated in vitro and in vivo by specific miRNAs

Abstract: SUMMARYSkeletal muscle is composed by different myofiber types that can preferentially use glycolysis or lipids for ATP production. How fuel preference is specified in these post-mitotic cells is unknown. Here we show that miRNAs are important players in defining the myofiber metabolic profile. mRNA and miRNA signatures of all myofiber types obtained at single cell level unveiled fiber-specific regulatory networks and identified two master miRNAs that coordinately control myofiber fuel preference and mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…The transcription factors PPARA and Estrogen Related Receptor Beta (ESRRB) are mediating fatty acid degradation and oxidative metabolism (73,103,104). Similar roles are known for additional members of their respective families (105,106).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The transcription factors PPARA and Estrogen Related Receptor Beta (ESRRB) are mediating fatty acid degradation and oxidative metabolism (73,103,104). Similar roles are known for additional members of their respective families (105,106).…”
Section: Discussionmentioning
confidence: 97%
“…The sorting is important since only less than 60% of the cell nuclei in muscle tissue are myonuclei (22,24), and the sorting excluded When we compared myonuclei from the two extreme muscles soleus and EDL we found that they had a large part of the epigenome in common. Important differences were found in connection to genes coding for proteins involved in contraction, calcium handling and metabolic pathways; reflecting differences at the transcriptional and protein level between different fiber types (41,64,(73)(74)(75).…”
Section: Discussionmentioning
confidence: 99%